DOP83 Normalisation of biomarkers and improvement in clinical outcomes in patients with Crohn's Disease treated with risankizumab in the phase 3 ADVANCE, MOTIVATE, and FORTIFY studies. (21st January 2022) - Atreya, R; Feagan, B; Shchukina, O; Jairath, V; Rieder, F; Hisamatsu, T; Siegmund, B; Rizzo, J; Kligys, K; Neimark, E; Song, A; Zambrano, J; et al.
Abstract: Background: The efficacy of risankizumab (RZB), an interleukin 23 p19 inhibitor, in patients with Crohn's disease (CD) has been reported. Normalisation of high-sensitivity C-reactive protein (hs-CRP) and faecal calprotectin (FCP) are intermediate treatment targets in CD. Here, we evaluated changes in these objective inflammatory biomarkers and clinical outcomes with RZB treatment. Methods: In 2 phase 3, randomised, double-blind studies (ADVANCE, NCT03105128; MOTIVATE, NCT03104413), patients with moderately to severely active CD received 12-week intravenous (IV) RZB induction therapy or placebo (PBO). Patients with clinical response to RZB IV induction were rerandomised in a 52-week maintenance study (FORTIFY, NCT03105102) to receive subcutaneous (SC) RZB or PBO (ie, RZB withdrawal). Induction analyses included patients who received either 600 mg RZB IV or PBO for 12 weeks. Maintenance analyses included patients who received 360 mg RZB SC every 8 weeks or withdrawal (PBO SC) for 52 weeks. Outcomes assessed were normalisation of hs-CRP and FCP concentrations at week 12 of induction and at week 52 of maintenance in patients with elevated biomarkers at baseline (hs-CRP > 5 mg/L and/or FCP > 250 μg/g), clinical biomarker response (defined as enhanced clinical response [≥ 60% average daily stool frequency (SF) decrease and/or ≥ 35% average daily abdominal pain score (APS) decrease] and ≥ 50% reduction in hs-CRP or FCP), and clinical biomarker remission (defined as clinical remission per CD Activity Index or SF/APS criteria and normal hs-CRP or FCP) during maintenance treatment. Nonresponder imputation was used for missing data. Results: Greater proportions of patients receiving RZB vs PBO achieved normalisation of hs-CRP and FCP at the end of the 12-week induction period and the 52-week maintenance period ( P < .0001 for all; Table ). Among patients with clinical response to RZB IV induction and entered maintenance, rates of clinical biomarker response were maintained through week 52 in patients receiving 360 mg RZB SC and declined over time among patients in the withdrawal (PBO SC) arm (Figure A ). Rates of clinical biomarker remission increased over time in patients receiving 360 mg RZB SC. At week 52, clinical remission and normalisation of hs-CRP or FCP was achieved by 41% of patients receiving RZB vs 28%–29% of patients in the withdrawal (PBO SC) arm (Figure B-C ). The safety profile of RZB in CD was previously reported. Conclusion: Normalisation of objective biomarkers of inflammation in CD was achieved with RZB induction and maintenance therapy. Improvements in both clinical outcomes and biomarker levels were sustained with continuous RZB maintenance therapy and decreased over time in patients discontinuing RZB.